Rights and access to plant genetic resources under India's new law - Ramanna, Anitha; Smale, Melinda (Wiley, 2004)
Recognition of ‘Farmer's Rights’ is an attempt by developing countries to evolve a counterclaim to breeders' Intellectual Property Rights (IPRs) promoted under the TRIPs Agreement of the WTO. India is one of the first countries to have granted rights to both breeders and farmers under the Protection of Plant Varieties and Farmers' Rights Act, 2001. This multiple rights system aims to distribute rights equitably, but may pose the threat of an ‘anticommons tragedy’ i.e. too many parties independently possessing the right to exclude others from utilising a resource. If under‐utilisation of plant genetic resources results, the Act will have negative consequences for sustaining crop productivity and for the welfare of the very farming communities it seeks to compensate.